The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1177/0022034511415275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mechanical Loading on Electrical Conductivity in Porcine TMJ Discs

Abstract: The objective of this study was to examine the impact of mechanical loading on solute transport in porcine temporomandibular joint (TMJ) discs using the electrical conductivity method. The electrical conductivity, as well as ion diffusivity, of TMJ discs was determined under confined compression with 3 strains in 5 disc regions. The average electrical conductivity over the 5 regions (mean ± SD) at 0% strain was 3.10 ± 0.68 mS/cm, decreased to 2.76 ± 0.58 mS/cm (-11.0%) at 10% strain, and 2.38 ± 0.55 mS/cm (-22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 30 publications
4
26
1
Order By: Relevance
“…This is likely because meniscus composition is most like that of TMJ tissue, which also has a relatively low GAG content as compared to articular cartilage or intervertebral disc (Almarza and Athanasiou, 2004). The strain-dependent behavior of electrical conductivity and relative ion diffusivity found here is similar to results in the literature for other cartilaginous tissues (i.e., meniscus, articular cartilage, intervertebral disc, TMJ), which showed that static compression leads to reduced solute diffusivity and/or electrical conductivity Jackson et al, 2008;Kleinhans et al, 2015;Kuo et al, 2011;Quinn et al, 2000;Quinn et al, 2001;Wright et al, 2013;Yuan et al, 2009). This change is likely due to reduced tissue water content caused by fluid exudation during compression.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…This is likely because meniscus composition is most like that of TMJ tissue, which also has a relatively low GAG content as compared to articular cartilage or intervertebral disc (Almarza and Athanasiou, 2004). The strain-dependent behavior of electrical conductivity and relative ion diffusivity found here is similar to results in the literature for other cartilaginous tissues (i.e., meniscus, articular cartilage, intervertebral disc, TMJ), which showed that static compression leads to reduced solute diffusivity and/or electrical conductivity Jackson et al, 2008;Kleinhans et al, 2015;Kuo et al, 2011;Quinn et al, 2000;Quinn et al, 2001;Wright et al, 2013;Yuan et al, 2009). This change is likely due to reduced tissue water content caused by fluid exudation during compression.…”
Section: Discussionsupporting
confidence: 81%
“…Due to the low GAG content ( $ 2-3% dry weight) in meniscus compared to other cartilaginous tissues, it was considered an uncharged tissue. The relative diffusivity (D=Do) of NaCl can be related to the conductivity measurements by (Gu et al, 2004;Kuo et al, 2011;Wright et al, 2013):…”
Section: Relative Ion Diffusivitymentioning
confidence: 99%
See 3 more Smart Citations